2018
DOI: 10.1158/1078-0432.ccr-18-0945
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of ALT-803, A Novel Recombinant IL15 Complex, in Patients with Advanced Solid Tumors

Abstract: IL15 induces the activation and proliferation of natural killer (NK) and memory CD8 T cells and has preclinical antitumor activity. Given the superior activity and favorable kinetics of ALT-803 (IL15N72D:IL15RαSu/IgG1 Fc complex) over recombinant human IL15 (rhIL15) in animal models, we performed this first-in-human phase I trial of ALT-803 in patients with advanced solid tumors. Patients with incurable advanced melanoma, renal cell, non-small cell lung, and head and neck cancer were treated with ALT-803 0.3 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 16 publications
3
127
0
2
Order By: Relevance
“…Recent studies in mice have shown greater tissue biodistribution of N-803 to lymphoid organs when administered by subcutaneous administration as compared to intravenous administration [19]. In humans, subcutaneous versus intravenous administration resulted in a significantly longer serum half-life, decreased serum levels of pro-inflammatory cytokines, as well as sustained and significantly increased activation and proliferation of both NK cells and CD8+ T cells [20,21]. We have thus adjusted our dosing route for the current study from intravenous to subcutaneous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in mice have shown greater tissue biodistribution of N-803 to lymphoid organs when administered by subcutaneous administration as compared to intravenous administration [19]. In humans, subcutaneous versus intravenous administration resulted in a significantly longer serum half-life, decreased serum levels of pro-inflammatory cytokines, as well as sustained and significantly increased activation and proliferation of both NK cells and CD8+ T cells [20,21]. We have thus adjusted our dosing route for the current study from intravenous to subcutaneous.…”
Section: Resultsmentioning
confidence: 99%
“…We previously defined that intravenous injection of N-803 triggers the influx of CD8+ T cells into lymph nodes of SIV-infected rhesus macaques [13]. Recent reports have compared the safety, tolerability, pharmacokinetics, immunologic events, and biodistribution between subcutaneous and intravenous routes of N-803 administration [21,29]. Although subcutaneous N-803 administration leads to 100-fold less serum concentrations compared to intravenous administration, it exhibits greater biodistribution to lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Like TLR agonists, the use of recombinant cytokines, such as IL-12 [192], which is essential for STAT4-driven Th1 differentiation and the cytolytic function of effector T cells, and IL-15 [193], reported to increase NK cell activation and T cell expansion via STAT5 activation, have yielded successful outcomes in preclinical settings. Several phase I trials utilising the IL-15 superagonist ALT-803 as a monotherapy [193,194] or in conjunction with anti-PD1 [195] have recently commenced, with early reports of patient tolerance, immune activation, and antitumor activity disclosed in metastatic melanoma and NSCLC. Likewise, high-dose IL-2 has been under scrutiny in metastatic melanoma and renal cell carcinoma [196,197] for decades, with reports of disease stabilization and regression [198,199].…”
Section: Cytokine Receptor Targetingmentioning
confidence: 99%
“…In preclinical studies, ALT-803 enhanced memory CD8 + T cell subpopulations and specific NK expansion, promoted the secretion of IFN-γ, and improved NK cell function in multiple animal models, including B cell lymphoma, glioblastoma, colon cancer, and ovarian cancer (60)(61)(62). Phase I or II clinical trial evaluating its safety and efficacy in patients with both hematological neoplasms (e.g., relapsed or refractory multiple myeloma, acute myelogenous leukemia, acute lymphoblastic leukemia, and myelodysplastic syndromes) and solid tumors (NCT01885897, NCT01946789, NCT02099539, NCT03054909) (63,64) or in combination with NK cell adoptive therapy (NCT02465957, NCT02890758), or with nivolumab (NCT02523469) (65) are currently ongoing. New expansion methods are being exploited to obtain large numbers of NK cells with enhanced cytotoxic activity (66).…”
Section: Cytokine-activated Nk Cells In Tumor Immunotherapymentioning
confidence: 99%